Поселення заключного етапу доби бронзи в басейні нижньої течії Сіверського Дінця та на Донецькому кряжі: археологічна карта регіону - Пробийголова, О.С. (Археологія і давня історія України, 2018)
В основу картографування поселень заключного періоду доби бронзи в басейні нижньої течії Сіверського Донця та на Донецькому кряжі покладені матеріали розвідок близько 800 пам'яток. Характер розташування поселень другого етапу бережнівсько-маївської зрубної культури та постзрубного часу засвідчує достатньо щільну заселеність території наприкінці доби бронзи. The paper is devoted to the mapping of the Late and
Final Bronze Age settlements that are situated in the
basin of the river Siverskiy Donets and on the Donets
Ridge. On the basis of analyses more than 800 Late
Bronze Age settlements the horizon of the late stage
Berezhnovka-Maevka Srubnaya culture and post-
Srubnaya settlements horizon were identified.
The Late Bronze age settlements are evenly spread
over the territory of the basin of the river Siverskiy Donets
and on the Donets Ridge. The Final Bronze age localities
are the same to the previous stage. On the contrary, the
Bondarikhinskaya culture settlement’s location differs from the post- Srubnaya sites. All of them are located on
the left bank of the river Siverskiy Donets and none of them are situated on the right bank. The location of settlements
indicates a high population density in the basin of the river Siverskiy Donets and on the Donets Ridge during
the Bronze age from the first stage of Berezhnovka-Maevka Srubnaya culture and to the end of the Bronze Age.